Narrative Policy Framework: Media's Role in 2024 Local Leaders Election Policy - Satria, Teguh; Qodir, Zuly (Mediator: Jurnal Komunikasi, 2024)
The research aims to analyze the strategic role of the media in shaping the narrative of the 2024 simultaneous regional head elections in Indonesia, focusing on how the media influences people's perceptions and political decisions. This research used a qualitative method, employing the Media Role Narrative approach by collecting and analyzing data from Kumparan, Detik, and Kompas media. NVivo 12 Plus was utilized to systematically manage and analyze qualitative data, allowing researchers to identify narrative patterns and themes from many news articles efficiently. Using the ‘Crosstab Query’ and ‘Word Cloud’ features of NVivo 12 Plus, the researchers could see that narratives related to specific candidates, such as corruption allegations against one of the regional head candidates, were often repeated in Kompas and Detik news articles. The results revealed that the media has a role in shaping election narratives, but previous literature demonstrates that its influence on election outcomes tends to be indirect and non-deterministic. This study provides new insights into the impact of media narratives in the context of local elections, revealing how narratives can be directed to strategically influence public opinion. It also offers a policy framework that can support the creation of fair and balanced narratives in the context of local democracy.